Análisis y evaluación al desempeño del talento humano del área administrativa del gobierno autónomo descentralizado municipal del cantón Macará, provincia de Loja, para el año 2016 - Rodríguez Jaya, Mercy Yanira (2017)
The Human Talent Performance Evaluation is very important for all types of organizations, whether public or private, as it is a tool that allows evaluating and judging the value, excellence and qualities of human resources within the institution. This dissertation work entitled "ANALYSIS AND EVALUATION OF THE PERFORMANCE OF THE HUMAN TALENT OF THE ADMINISTRATIVE AREA OF THE AUTONOMOUS DECENTRALIZED GOVERNMENT OF CANTÓN MACARÁ, PROVINCE OF LOJA, FOR THE YEAR 2016", was carried out because in this entity its personnel has not being evaluated in terms of Human Talent Performance, this being a fundamental element not only from the productive point of view, but also in the social point of view, since this model of analysis would provide a support mechanism where it is directed to the fulfillment and satisfaction of planned purposes by the Municipality. In addition fundamental purpose to know the degree of fulfillment of the functions performed by each one of the human talent of the entity and in turn determine the existing work climate in the same. For the development of the research work it was necessary to propose a general objective in order to carry out an analysis and evaluation of the Human Talent Performance of the Administrative Area of the GAD of the Macará canton and four specific objectives: To make a diagnosis the current situation of the human performance of the Area Administrative of the AAutonomous Government Decentralized Municipal of the canton. Identify the positions, functions, compliance indicators and evaluation criteria of the performance of the positions and establish proposals for improvement in relation to the results found in the evaluation of the performance of each position of the management under study. The methodology used for the development of the thesis was based on the following methods: deductive, inductive, analytical, statistical and bibliographic; in turn the following observation techniques were used: direct, interview and finally the survey to obtain the necessary information, which provided a clear and reliable vision of this institution. As for the results obtained from the analysis of the staff of the Municipal Decentralized Autonomous Government of Canton Macará, it was possible to conclude the respective factors applied in the evaluation: The evaluation was applied to the 8 public servants of the Autonomous Government Decentralized of the Canton Macará, considering the following scale of qualification: of 21-25 points = Excellent; 16-20 = Very Good; 11-15 = Good; 6-10 Points = Unsatisfactory and 1-5 Points = Poor. The quantitative results vary from 20 to 25 points, evidencing that the personnel who work in this area, is in a level of performance between excellent and very good; which means that each of the public servants carry out the tasks entrusted to them efficiently. In the survey applied to measure the level of employee satisfaction, it was identified that among the factors to be improved with a percentage of 71% of dissatisfaction is the fear of being expressed and that employees are unaware of which positions they can aspire to within the entity should ; so that proposals are presented to improve how to promote the institutional development of the Macao GAD collaborators, encouraging them through promotions and providing adequate resources so that the collaborators can address the issues related to their work, in addition to being recommended emphasize the performance and frequent evaluation of staff for the benefit of the municipality as such.